Homemade production of fermented beverages: a biotechnological alternative to improve health in brazilian poor communities (Research, Society and Development, 2023)
This study presents the possibility of increasing the consumption of fermented beverages, such as kombucha and water kefir, to improve health in poor communities in Brazil. The objective is to demonstrate the importance of making efforts to make these healthy beverages widely available, especially for populations at high risk of morbidity and mortality, replacing the excessive consumption of soft drinks. The qualitative methodological approach used characterizes the study as a bibliographic review. The study's conclusions indicate that strategies should be adopted that emphasize to consumers the problems related to the excessive consumption of beverages and foods with high sugar content and encourage the replacement of conventional soft drinks by healthy beverages. In addition, it points out as a perspective the development of educational actions, such as workshops on homemade production of fermented beverages, in order to teach the population about the benefits of functional foods and beverages for health. Finally, it is positioned as reference material for further discussions and future elaboration of public policies that encourage the production and consumption of these beverages by the Brazilian population.